The effect of six weeks of sling exercise training on trunk muscular strength and endurance for clients with low back pain - You, Yu-Lin (J Phys Ther Sci, 2015)
[Purpose] The purpose of this study was to investigate the effects of 6 weeks sling exercise training for clients with low back pain on the levels of pain, disability, muscular strength and endurance. [Subjects and Methods] Twelve chronic LBP subjects participated in this study. Subjects were randomly divided into a control group and a training group. Subjects in the training group performed sling exercise training for six weeks, and participants in the control group did not perform any exercise. [Results] Pain, disability levels and muscular strength significantly improved in the training group, but not in the control group. The left multifidus showed a significant improvement in muscular endurance, measured as the slope of the median frequency after training. [Conclusion] Six weeks of sling exercise training was effective at reducing pain intensity, and improving the disability level and trunk muscular strength of subjects with low back pain.